КӘСІПОРЫННЫҢ ҚАРЖЫЛЫҚ ЖАҒДАЙЫН БАҒАЛАУДЫ ЖЕТІЛДІРУ ЖОЛДАРЫ (Journal of Economic Research & Business Administration, 2015)
Theoretical value of a financial position and financial stability of the enterprise is defined. Main objectives of the program of anti-recessionary management are revealed. Maintenance of financial stability, crisis prevention – are a component of management and strategic planning against bankruptcy.